Synthesis of lactones from fatty acids by ring-closing metathesis and their biological evaluation - Yelchuri, Vyshnavi; Azmeera, Thirupathi; Karuna, Mallampalli Sri Lakshmi (European Journal of Chemistry, 2023)
The present study involves the synthesis of macrocyclic lactones by the esterification of unsaturated fatty acids (oleic acid, undecenoic acid, and erucic acid) with unsaturated alcohols (allyl alcohol, prop-2-ene-1-ol, oleyl alcohol, and undecenol) followed by a ring closing metathesis reaction employing Grubbs’ second generation catalyst (1.0-1.5 mmol). The structure of the compounds was confirmed by 1H NMR, 13C NMR, FT-IR, and ESI-Mass spectral studies. The antibacterial activity of the synthesised lactones was evaluated. The larger ring-sized lactone, namely, erucic acid lactone, exhibited excellent antibacterial activity against three bacterial cell lines, namely, Staphylococcus aureus, Staphylococcus epidermidis, and Bacillus subtilis. Undecenoic acid-based lactones exhibited excellent antibacterial activity selectively against only Staphylococcus epidermidis. The assay of macrolactones for their in vitro anticancer activity was carried out by MTT for different cancer cell lines, namely, human prostate epithelial cancer cells (ATCC HTB-81), HepG2 derived from hepatic cancer cells (ATCC HB-8065), SKOV3 derived from human ovarian cancer cells (ATCC HTB-77), MDAMB-231 derived from human breast cancer cells (ATCC HTB-26) and Chinese hamster ovarian (CHO-K1) cell lines. The molecules selectively exhibited anticancer activity against Chinese hamster ovarian (CHO-K1) cell lines. Among macrolactones, (E)-oxacyclotridec-11-en-2-one (MALUN) was more active and its activity was much higher compared to others and on par with the reference standard Mitomycin C. This was followed by (E)-oxacyclotricos-14-en-2-one (MOLER) and (E)-oxacyclononadec-10-en-2-one (MOLOH). The fatty acid-based cyclic lactones with selective antibacterial and anticancer activities can be further explored for a variety of pharmaceutical formulations.